Share Value Of Halal Food Product Company And Its Independent Factors - Kaban, Reny Fitriana; Evi, Tiolina; Hadi, Ibrahim (Indonesian Scientific Publication, 2024)
Introduction/Main Objectives: This article aims to analyze the value of halal food product companies whose shares are listed on the Jakarta Islamic Index 70 during the period 2020 to 2022 and independent factors that influence it. It is necessary to carry out an analysis of the factors that influence the share value of sharia food product companies to provide investors with an overview of the performance of halal food product company shares to obtain an increase in investment value in this type of share which ultimately helps the development of the halal food industry in Indonesia and can be a reference for the development of the halal food industry in other ASEAN countries and the world. Research Methods: Research data was obtained from the Indonesia Stock Exchange website in the form of financial reports and the research method used was quantitative, starting with descriptive tests and then continuing with multiple linear regression tests. Finding/Results: From the research results, it was found that the average value of halal food product companies whose shares are registered on JII 70 is still overvalued, and tends to decline, while the average profitability value is good, but this is not the case with the leverage value which is in the warning category. Profitability and leverage factors are proven to influence company value. Conclusion: It is recommended that players in the halal food product industry hope to improve their financial performance and be more anticipatory of all existing risks such as pandemics or other crises, to increase the sustainability of investor confidence.